Rice Noodles: Materials, Processing and Quality Evaluation: Rice Noodles: Materials, Processing and Quality Evaluation - Ahmed, Ishfaq; Qazi, Ihsan Mabood; Li, Zhenxing; Ullah, Javid (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Asian peoples consume noodles as a staple food since ancient time. It is convenient, easy to cook, delicious and nutritionally rich product and is now gaining great appraisal outside Asia also. Generally, rice noodles are prepared from flour, salt, water and various optional ingredients. Rice flour is kneaded in the presence of water and salt to form dough and is then sheeted, compounded, steamed and cut to form a noodle strands. The noodle strands can be further processed (dried, fried, boiled and frozen) to develop various types of noodles based on consumer preferences. This review article focus on different ingredients and their functionality as well as the processes involved in transforming raw material to finished product. Protein, ash, dough strength and amylose concentration are very crucial regarding noodle quality. Variation in compositions affects the cooking, functional and eating properties of noodles. Due to the absence of gluten, rice noodles have less cohesive and extensive texture. Steaming gelatinizes rice starches up to some extent, which aids in the partial compensation of gluten role in rice based noodles. The trend towards gluten free noodle is due to their health beneficial effect as they help in lowering the risk of allergic reactions and celiac diseases, as well as induce lower glycemic index for patients suffering from diabetics. High quality noodle must be bright in color, have an adequate shelf life without oxidative rancidity or microbial spoilage, and have good textural and cooking properties.